Hubungan Pengetahuan, Sikap dan Dukungan Keluarga Dengan Kepatuhan Ibu Hamil Trimester III Mengkonsumsi Tablet Besi (Fe) di Wilayah Kerja Puskesmas Karang Mukti Kecamatan Lalan Tahun 2021 - Yeni Aimi; Rizki Amalia; Siti Aisyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In Indonesia, there are 41 cases of anemia in pregnant women every day, and 20 women die due to anemia. This high number is due to the low ignorance of the mother about the dangers of anemia in pregnancy which tends to appear in the 1st and 3rd trimesters of pregnancy. Aims to determine the relationship between Knowledge, Attitude and Family Support with the Compliance of Pregnant Women in the Third Trimester Consuming Iron (Fe) Tablets in the Work Area of Karang Mukti Health Center, Lalan District. This type of research is an analytical survey using a cross sectional approach design. The population in this study were all mothers in the third trimester of 2021, which amounted to 186 people and the number of samples was 65 respondents. The sampling technique used was purposive sampling. Analysis of the data used is the chi-square statistical test with p value value (0.05). The results of this study from 65 respondents, there is a relationship between knowledge and adherence of pregnant women to consume Fe tablets, p value = 0.000, there is a relationship between attitudes and adherence to pregnant women taking Fe tablets, p value = 0.02 and there is a relationship between family support and compliance with pregnant women taking tablets. Fe p value = 0.03. It is expected to be able to improve health services to the community through various methods, both health counseling to reduce maternal mortality.